Penerapan Metode Just In Time dalam Upaya Meningkatkan Efisiensi Biaya Produksi Optimal pada UD. Rambak Dudung di Desa Ambal Ambil - Nurul Hidayat; Misbach Munir (MES Bogor, 2024)
A trading business is a business that is engaged in buying and selling products. Trading businesses can engage in various types of products that are sold for consumer, business, or government purposes. One of them is UD. Rambak Dudung is trying to buy raw materials in large quantities to keep in store if the supply runs out and demand in the market increases. With the excess of raw materials, it can cause storage costs, which can reduce UD's profits. aforementioned. So this shows that the supply of raw materials is a fairly big problem. This study aims to determine the application of the Just in time method to UD. Rambak Dudung and knew the role of the Just in time method in improving production cost efficiency in UD. Rambak Dudung. The type of research used is a descriptive method with a quantitative approach. Data collection was carried out by interviews, internet searches and library studies. The data processed is the purchase and use of raw materials. The calculation technique used is to calculate the total production cost based on company policies, the EOQ method, and the JIT/EOQ method. Based on the results of the calculation, it was concluded that the inventory policy carried out by the company has not been maximally seen from the total production costs incurred of Rp.5,853,500,- compared to the JIT/EOQ method of Rp.2,588,436,- so that the total cost saved is Rp.3,265,064.